The Unity of Plutarch's Work 'Moralia' Themes in the 'Lives', Features of the 'Lives' in the 'Moralia' - Nikolaidis, Anastasios (Millennium-Studien / Millennium Studies, 2008)
The contributions to this volume inquire into many important issues of Plutarchean scholarship: the conditions under which Plutarch`s writings were split into two distinct corpora, his methods of work and the various authorial techniques employed, the interplay between Lives and Moralia, Plutarch and politics, Plutarch and philosophy, literary aspects of Plutarch`s œuvre, Plutarch on women, Plutarch in his epistemological and socio-historical context. The contributors offer in-sights that throw new light on Plutarch`s personality and illustrate the unity of his varied literary production.